Triticum aestivum L. group aestivum CGN06327 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. group aestivum Common name(s): wheat Other names: Orca, M.G.H. 50-14 Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN06327 Method of creation: Acquisition Date: 1987-06-12 Other identifiers: purl,http://purl.org/cgngenis/accenumb/CGN06327, n/a,MGH 50-14 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...